Trash crisis on earth - Stadler, Alexander (New York Scholastic Press, 2008)
Eight-year-old Julian Rodriguez escapes from the crisis of the moment (being sent to his room for not taking out the trash) by imagining he is a space warrior
Hurg
5
NEW_HUR_GN
Keywords: Behavior -- Fiction; Extraterrestrial beings -- Fiction; Humorous stories; Imagination -- Fiction